Work-Unit Absenteeism: Effects of Satisfaction, Commitment, Labor Market Conditions, and Time - Hausknecht, John P.; Hiller, Nathan J.; Vance, Robert J. (Academy of Management Journal, 2008)
Prior research is limited in explaining absenteeism at the unit level and over time. We developed and tested a model of unit-level absenteeism using five waves of data collected over six years from 115 work units in a large state agency. Unit-level job satisfaction, organizational commitment, and local unemployment were modeled as time-varying predictors of absenteeism. Shared satisfaction and commitment interacted in predicting absenteeism but were not related to the rate of change in absenteeism over time. Unit-level satisfaction and commitment were more strongly related to absenteeism when units were located in areas with plentiful job alternatives.